CERKL mutation causing retinitis pigmentosa(RP) in Indian population – a genotype and phenotype correlation study. (1st November 2020) - Sen, Parveen; Maitra, Puja; Natarajan, Srikrupa; Sripriya, Srivatsan; Mathavan, Sinnakaruppan; Bhende, Muna; Manchegowda, Pradeep T
ABSTRACT: Background: Mutations in CERKL gene has been reported to cause Retinitis pigmentosa (RP) and clinically appears discrete from other commonly encountered phenotypes. We report 14 patients who were seen to have CERKL mutation of the 152 patients of RP from Indian population who underwent genetic testing. Materials and Methods: A retrospective analysis was performed in 28 eyes of the 14 unrelated patients to establish genotype phenotype correlation. Targeted next generation sequencing was performed using the STRAND® NGS v2.5 software. Validation was done using PCR-based bidirectional Sanger sequencing. Clinical data was collected along with imaging such as fundus photo, autofluorescence(AF), Optical coherence tomography and Electroretinogram wherever available. Results: Three variants c.1045_1046delAT, c.847 C > T and a novel c.899-IG>A were identified. Retinal morphological features were typically bilaterally symmetrical with mild to moderate disc pallor and arteriolar attenuation in all cases, while sparse peripheral pigmentation was noted in seven patients indicating paucipigmentary character. Early macular involvement in all cases was a characteristic finding with central hypo-autofluorescence and surrounding hyper-autofluorescence. Peripheral scalloped chorioretinal atrophic patches were seen in five patients particularly in older patients. Conclusions: Phenotype associated with CERKL mutation appears clinically discrete from other commonly encountered phenotypes of inherited retinal dystrophies. Recognizing this typical genotype phenotype correlation will help clinicians to identify this form of RP, prognosticate the disease and segregate candidates for futures gene therapy.